THE REDUCTION OF FRICTIONAL RESISTANCE IN THE CURVES - Kossov, V. S.; Panin, Yu. O. (Science and Transport Progress, 2004)
The concept of combined rail lubrication, the results of theoretical and experimental researches of its efficiency are considered.